Review of sukuk on blockchain - Adam Sa'ad, Auwal; Sherin, Kunhivaba; Aishath, Muneeza; Ershadul, Karim; Zakariya, Mustapha (2019)
As an offshoot of the fourth industrial revolution (Industry 4.0), the use of technology to produce and/or deliver financial products (fintech) is pervasively disruptive of traditional institutions and operations as manifested in innovative entities, products and services powered by such technologies as artificial intelligence (AI) and smart contracts on blockchain etc. The blockchain technology and smart contracts are financial technologies of significant impact in this regard. A blockchain is a decentralised, distributed and digital ledger that is used to record transactions across many computers so that any involved record cannot be altered retroactively, without change to all subsequent blocks. A smart contract encodes business rules agreed by the parties directly into the underlying transaction itself and the blockchain itself enforces the contract rules. The use of blockchain technology and smart contracts, while revolutionising the financial services industry also presents opportunities for production and delivery of an important ICM product i.e. sukuk (Islamic bond). Derived from the singular Arabic word ‘sakk’, sukuk is literally a certificate that confirms a transaction stipulating the rights and conditions of contracting parties. It is also defined as certificates of equal value evidencing undivided ownership or investment in an assets using Shariah principles and concepts endorsed by the Shariah advisors.